Myocardial work index during normal dobutamine stress echocardiography - Marina Leitman (Scientific Reports, 2022)
Abstract Dobutamine stress echocardiography is an alternative method to exercise stress echocardiography for the evaluation of ischemia. Recently, the novel speckle tracking imaging derived parameter, myocardial work index, was suggested for the evaluation of cardiac performance and was evaluated during exercise stress echocardiography. In this study, we analyzed the effect of dobutamine on myocardial work index variables during normal dobutamine stress echocardiography. Echocardiography examinations of patients with normal dobutamine stress echocardiography were collected and underwent off-line speckle tracking imaging analysis. Myocardial work index parameters were calculated at each dose of dobutamine and compared. 286 patients underwent dobutamine stress echocardiography during the study period. 102 patients were excluded due to pre-existed coronary artery disease or ischemia at dobutamine stress echocardiography. 65 patients were excluded due to suboptimal image quality unsuitable for speckle tracking imaging analysis. The remaining 119 patients with normal results were included. The global work index decreased from 2393.3 to 1864.7 mmHg%, p < 0.0004. Global constructive work decreased from 2681.7 to 2152.6 mmHg%, p = 0.001. Global wasted work increased from 78.8 to 128.3 mmHg%, p < 0.003. Global work efficacy decreased from 96.1 to 91.9%, p < 0.00001. Global strain increased from—19.6 to − 23.7%, p < 0.00001. Dobutamine stress echocardiography results in a decrease of all specific myocardial work index parameters even in normal subjects. Only global myocardial strain improved.